Evidence on the Varying Effect of Expected Inflation On Interest Rates - VanderHoff, James (The Review of Economics and Statistics, 1984)
Boskin, Michael J., Mark Gertler, and Charles Taylor, Impact of Inflation on U.S. and International Competitiveness (Washington, D.C.: National Planning Association, 1980). Carlton, Dennis W., The Disruptive Effect of Inflation on the Organization of Markets, in Robert E. Hall (ed.), Inflation: Causes and Effects (Chicago: University of Chicago Press, 1982). Fama, Eugene, Short-term Interest Rates as Predictors of Inflation, American Economic Review 65 (June 1975), 269-282. Freund, William C., and Paul B. Manchester, Productivity and Inflation, in John D. Hogan (ed.), Dimensions of Research, Vol. I (Houston: American Center, 1980), 53-71. Geweke, John, Richard Meese, and Warren T. Dent, Comparing Alternative Tests of Causality in Temporal Systems: Analytic Results and Experimental Evidence, Journal of Econometrics 21 (Feb. 1983), 161-194. Granger, C. W. J., Investigating Causal Relations by Econometric Models and Cross-Spectral Methods, Econometrica 37 (July 1969), 424-438. Guilkey, David K., and Michael K. Salemi, Small Sample Properties of Three Tests for Granger-Causal Ordering in a Bivariate Stochastic System, this REVIEW 64 (Nov. 1982), 668-680. Houthakker, Hendrik S., Growth and Inflation: Analysis by Industry, Brookings Papers on Economic A ctivity (1979), 241-256. Hsiao, Cheng, Autoregressive Modelling and Money-Income Causality Detection, Journal of Monetary Economics 7 (1981), 85-106. , Autoregressive Modeling and Causal Ordering of Economic Variables, Journal of Economic Dynamics and Control 4 (1982), 243-259. Jarrett, J. Peter, and Jack G. Selody, The Productivity-Inflation Nexus in Canada, 1963-1979, this REVIEW 64 (Aug. 1982), 361-367. Kendrick, John W., and Elliot S. Grossman, in the United States: Trends and Cycles (Baltimore: Johns Hopkins University Press, 1980). Sims, Christopher A., Money, Income and Causality, American Economic Review 62 (Sept. 1972), 540-552. U.S. Department of Commerce, Bureau of Economic Analysis, National Income and Product Accounts of the United States, 1929-76, Statistical Tables (Washington, D.C.: Superintendent of Documents, 1981). U.S. Department of Labor, Bureau of Labor Statistics, tables headed Analytical Ratios for the Business Sector, All Indexes 1977 = 100, and Basic Industry Data for the Business Sector, All Persons, printout dated April 27, 1983.